Impact of patient decision aids on appropriate and timely access to hip or knee arthroplasty for osteoarthritis: a randomized controlled trial. Issue 1 (January 2016) - Stacey, D.; Taljaard, M.; Dervin, G.; Tugwell, P.; O'Connor, A.M.; Pomey, M.P.; Boland, L.; Beach, S.; Meltzer, D.; Hawker, G.
Summary: Objective: To evaluate the effectiveness of patient decision aids (PtDA) compared to usual education on appropriate and timely access to total joint arthroplasty in patients with osteoarthritis. Method: A randomized controlled trial (RCT) with patients undergoing orthopedic screening. Control and intervention arms received usual education; intervention arm also received a PtDA and a surgeon preference report. Wait times (primary outcome) were described using stratified Kaplan–Meier survival curves with patients censored at the time of death or loss to follow-up, and multivariable Cox proportional hazards regression. Secondary outcomes were compared using stratified Cochran-Mantel-Haenszel chi-squared tests. Results: 343 patients were randomized to intervention ( n  = 174) or control ( n  = 169). The typical patient was 66 years old, retired, living with someone, and 51% had high school education or less. The intervention was associated with a trend towards reduction in wait time (hazard ratio (HR) 1.25, 95% confidence interval (CI) 0.99–1.60, P  = 0.0653). Median wait times were 3 weeks shorter in intervention than in control at the community site with no difference at the academic site. Good decision quality was reached by 56.1% intervention and 44.5% control (Relative risk (RR) 1.25; 95% CI 1.00–1.56, P  = 0.050). Surgery rates were 73.2% intervention and 80.5% controls (RR 0.91: 95% CI 0.81–1.03) with 12 intervention (7.3%) and eight control participants (4.9%) returning to have surgery within 2 years ( P  = 0.791). Conclusion: Compared to controls, decision aid recipients had shorter wait times at one site, fewer surgeries, and were more likely to reach good decision quality, but overall effect was not statistically significant. Trials registration: The full trial protocol is available atClinicalTrials.Gov (NCT00911638 ).